Ultimate capacity of structural steel cross-sections under compression, bending and combined loading. (February 2015) - Liew, Andrew; Gardner, Leroy
Abstract: The Continuous Strength Method (CSM) is a strain based structural steel design approach which allows for the beneficial influence of strain hardening. The method has been previously developed for predicting compression and bending resistances in isolation. This paper describes extension of the method to enable the prediction of the ultimate cross-section resistance of I-sections and box sections under combined loading. At the core of the method is a base curve, which relates the deformation capacity of a cross-section to its cross-section slenderness. Deformation capacity is defined as the ratio of the maximum strain that a cross-section can endure relative to its yield strain. Knowing this limiting strain and assuming plane sections remain plane, the resistance of a cross-section to combinations of axial load and bending moments can be calculated, by integrating the stresses arising from a suitable strain hardening material model over the area of the cross-section. By considering a range of combinations of applied actions, analytical expressions and numerically derived interaction surfaces have been produced, which were then rationalised into simple expressions for use in design. The resulting CSM design predictions for box sections and I-sections have been compared with existing test data, and shown to give additional capacity over current design approaches and a reduction in scatter of the predictions.